The colonic interleukin-19 aggravates the dextran sodium sulfate/stress-induced comorbidities due to colitis and anxiety - Li, Qiongyu; Meng, Fantao; Ma, Xiangxian; Sun, Zhe; Dai, Juanjuan; Liu, Jing; Li, Dan; Cong, Peijia; Xu, Ruixue; Zhao, Di; Wang, Wentao; Wang, Dan; et al. (Frontiers in Immunology, 2023)
Comorbidities due to inflammatory bowel disease (IBD) and anxiety are commonly acknowledged; however, their underlying basis is unclear. In the current study, we first conducted a clinical retrospective analysis to identify the enhancive incidence rate of IBD before or after the epidemic of Corona Virus Disease 2019 (COVID-19), with higher Generalized Anxiety Disorder-7 (GAD-7), as well as poorer Gastrointestinal Quality of Life Index (GIQLI). Then, the dextran sodium sulfate (DSS) and chronic unpredictable stress (CUS)-induced IBD and anxiety comorbid models were established with the correlational relations between symptoms of IBD and anxiety-related behaviors. We found dysfunctional up-regulation of a new inflammatory factor interleukin (IL)-19 in the colon of DSS/CUS treated mice. Overexpression of IL-19 in colon induced anxious phenotypes, and accelerated the anxious condition and symptoms of colitis in the DSS/CUS model by promoting the expression of inducible nitric oxide synthase (iNOS), IL-1β, and IL-6 pro-inflammatory factors, and activating signal transducer and activator of transcription 3 (STAT3) signaling pathway in the colon. Furthermore, overexpression of IL-19 in the colon also reduced the expression levels of brain-derived neurotrophic factor (BDNF), extracellular signal-regulated kinase (ERK), and cAMP-response element binding protein (CREB) signaling pathways activity in the hippocampus. These results suggest that IL-19 was a pivotal player in DSS/CUS-induced comorbidities of colitis and anxiety with different signaling pathways for the colon and hippocampus, which provides a candidate gene to explore the pathophysiology of comorbidities due to colitis and anxiety.